ASSESSMENT OF SECURITY RISKS TO CRITICAL INFRASTRUCTURE WITHIN THE NATIONAL MINING SUBSECTOR - Nicolae Daniel FITA; Mila Ilieva OBRETENOVA; Marius Daniel MARCU; Dragos PASCULESCU; Adina TATAR; Teodora LAZAR (Fiabilitate şi Durabilitate)
The need to assess security risks on the national mining subsector, which owns and generates critical mining infrastructures, comes in the context in which the possible occurrence of energy blackout cases generates major issues of national interest, with European and NATO implications. As critical mining infrastructures may be vulnerable to internal and/or external threats, they must be thoroughly assessed in terms of ensuring and enhancing energy and national security in order to prevent potential national crises. The authors believe that addressing the national mining subsector is a strictly national security issue because the lack of coal or electricity produced by it can cause enormous damage to industry, the economy and state systems, which are almost entirely dependent on electricity.